A Histopathological and Immunohistochemical Analysis of Ameloblastic Fibrodentinoma - Ronell Bologna-Molina; Sirced Salazar-Rodríguez; Ana María Bedoya-Borella; Ramón Gil Carreón-Burciaga; Gabriel Tapia-Repetto; Nelly Molina-Frechero (Case Reports in Pathology)
Ameloblastic fibrodentinoma (AFD) is considered a mixed odontogenic tumor that is characterized by conserved epithelial and ectomesenchymal neoplastic components. AFD is composed of long narrow cords and islands of odontogenic epithelium; the epithelial strands lie in a myxoid cell-rich ectomesenchymal tissue with stellate-shaped fibroblasts that exhibit long slender cytoplasmic extensions that resemble dental papilla. The lesions show the presence of dysplastic dentin. Although AFD is a rare entity and its very existence is not completely accepted, based on the extent of histodifferentiation, it is considered to represent a stage between ameloblastic fibroma and ameloblastic fibroodontoma. This study aimed to provide a histopathological and immunohistochemical characterization of this infrequent tumor. A large panel of antibodies including amelogenin, Ck 19, calretinin, syndecan-1, E-cadherin, MSH2, histone H3, and Ki-67 was used to illustrate the nature of the tumor.